Promising Practice for Building Community through Mixed-Reality Simulation in Teacher Preparation - Emily Spitzman; Alexandra Balconi; Gia Renaud; Jeanne Ingle; Andrea Cayson (Journal of the Scholarship of Teaching and Learning, 2022)
Abstract: It is critical that pre-service teachers have exposure to practice in order to be successful in their future classrooms. This article describes a step-by-step process of implementing mixed-reality simulation in teacher preparation courses in order to provide teacher candidates with an almost-real classroom experience. Through using this mixed-reality simulation platform, teacher candidates teach student avatars who are being controlled by a live, behind-the-scenes person, trained to facilitate classroom scenarios. Following an overview of the implementation of this mixed-reality technological tool into their classes, authors share successes and challenges, highlighting some key takeaways for those considering integrating this into their future classes.